Amphetamine induces dopamine efflux through a dopamine transporter channel - Kahlig, Kristopher M. (National Academy of Sciences, 2005)
Drugs of abuse, including cocaine, amphetamine (AMPH), and heroin, elevate extracellular dopamine (DA) levels in the brain, thereby altering the activity/plasticity of reward circuits and precipitating addiction. The physiological release of DA occurs through the calcium-dependent fusion of a synaptic vesicle with the plasma membrane. Extracellular DA is cleared by uptake through the Na(+)/Cl(-)-dependent DA transporter (DAT). In contrast, the substrate AMPH induces nonvesicular release of DA mediated by DAT. Extracellular AMPH is generally believed to trigger DA efflux through DAT by facilitating exchange for cytosolic DA. Here, in outside-out patches from heterologous cells stably expressing DAT or from dopaminergic neurons, by using ionic conditions in the patch pipette that mimic those produced by AMPH stimulation, we report that AMPH causes DAT-mediated DA efflux by two independent mechanisms: (i) a slow process consistent with an exchange mechanism and (ii) a process that results in rapid (millisecond) bursts of DA efflux through a channel-like mode of DAT. Because channel-like release of DA induced by AMPH is rapid and contains a large number of DA molecules, with a single burst of DA on par with a quantum of DA from exocytotic release of a vesicle, this burst mode of release may play a role in the synaptic actions and psychostimulant properties of AMPH and related compounds. Unlike AMPH, the endogenous substrate DA, when present on both sides of the plasma membrane, inhibits this channel-like activity, thereby suggesting that the DAT channel-like mode cannot accumulate DA against a concentration gradient.